Desenvolvimento e avaliação de candidatos vacinais à base de proteínas da superfície celular de Sporothrix schenckii - Portuondo Fuentes, Deivys Leandro [UNESP] (2015)
Sporotrichosis is a subacute or chronic infection affecting humans and other mammals, caused by the Sporothrix schenckii species complex. The disease has a worldwide distribution, but is considered endemic in Brazil, mainly in the state of Rio de Janeiro, where the cat has become the main transmitting agent. The antifungal treatment is very long and often associated to adverse effects indicating the demand for preventive or more effective and safe therapeutic strategies. One of the more promissory approaches would probably be the prophylactic or therapeutic vaccination. This study evaluated the immunogenicity and toxicity of cell surface protein-based (CSP) vaccine candidates of S. schenckii stricto sensu. The CSPs isolated with dithiotreitol were characterized by electrophoresis, mass spectrometry and FungalRV adhesin predictor. The CSPs were formulated with two adjuvants, aluminum hydroxide (AH) or gel PetA, or used alone, in two concentrations. The obtained formulations (CSP10, CSP100, AH+CSP10, AH+CSP100, PetA+ CSP10 and PetA+ CSP100) were administered to Balb/C mice in two subcutaneous doses at 2 weeks interval. The serum obtained from each group 7 days after the second dose was used to analyze the immunogenicity of each formulation. All the serum obtained from vaccinated groups, except those from CSP10 and AH+CSP10 groups, reacted with a 47 kDa band, previously identified as the glycolytic enolase enzyme and predicted as an adhesin in the FungalRV program. Subsequently, we demonstrated the presence this protein in the cell wall of S. schenckii, suggesting its immunogenic role. The induction of IgG and IgG2a immunoglobulins was significantly higher with AH+CSP100 and PetA+CSP100 formulations with respect to CSP10, CSP100, AH+CSP10, and PetA+CSP10. The significant induction of IgG1 and IgG2a subtypes and IL-12, IFN-γ, IL4 and IL-17 by AH+CSP100, suggests a balance ...